CYBERSECURITY ETHICS AND LAW A REVIEW OF CURRENT CHALLENGES, FRAMEWORKS, AND FUTURE PERSPECTIVES - Jain, Dr. Nilesh (Journal of Global Research in Mathematical Archives(JGRMA), 2025)
In the evolving digital landscape, cybersecurity stands at the confluence of ethical responsibility, legal mandates, and technological innovation. This review paper critically examines the current state of governance in cybersecurity ethics by exploring the ethical challenges faced by researchers and practitioners, including concerns around data privacy, algorithmic accountability, surveillance, and AI governance. It evaluates existing legal and ethical frameworks, highlighting their limitations in addressing the dynamic nature of cybersecurity threats. Drawing upon recent studies and illustrative case examples, the paper advocates for the integration of ethics-by-design principles and adaptive legal frameworks as foundational strategies for responsible technology deployment. Furthermore, the analysis underscores the urgent need for interdisciplinary collaboration among technologists, ethicists, and legal professionals to navigate complex ethical dilemmas in cybersecurity. The paper concludes by outlining future directions, emphasizing global regulatory harmonization, flexible legal infrastructures, and embedding ethical norms into system architecture. This holistic approach is essential to fostering societal trust, safeguarding fundamental rights, and ensuring resilient cybersecurity in the face of rapid technological advancement.